1977
DOI: 10.1126/science.841339
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Human Diploid Cell Strain, IMR-90

Abstract: A new human diploid fibroblast-like cell line has been established from lung tissue of a female fetus. This has been frozen away in large quantity and characterized for use in research and related purposes. This is the first of a planned series of human cell lines to be established, characterized, and banked in large quantity in support of the National Institute on Aging research and general cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(140 citation statements)
references
References 14 publications
6
133
0
1
Order By: Relevance
“…IMR-90 human diploid lung ®broblasts (catalog #I90-P04) (Nichols et al, 1977) were obtained from the National Institute on Aging Cell Repository (Camden, NJ). Cells were grown in Dulbecco's modi®ed Eagle medium (Gibco BRL, Gaithersburg, MD) containing 10% iron-supplemented calf serum (Hyclone, Logan, UT) and 3.5 mM glutamine in a humidi®ed 5% CO 2 atmosphere at 378C.…”
Section: Cell Culturementioning
confidence: 99%
“…IMR-90 human diploid lung ®broblasts (catalog #I90-P04) (Nichols et al, 1977) were obtained from the National Institute on Aging Cell Repository (Camden, NJ). Cells were grown in Dulbecco's modi®ed Eagle medium (Gibco BRL, Gaithersburg, MD) containing 10% iron-supplemented calf serum (Hyclone, Logan, UT) and 3.5 mM glutamine in a humidi®ed 5% CO 2 atmosphere at 378C.…”
Section: Cell Culturementioning
confidence: 99%
“…The elevated level of actin RNA in this cell line (Fig. 3, lower left panel) as compared with the MNL samples probably relates to its fibroblastic origin (27).…”
Section: Methodsmentioning
confidence: 99%
“…These estimates of myc elevation are in rough agreement with the dot blot data. IMR-90 is a primary cell line (27) that contains nonelevated levels of myc RNA based on dot blot hybridization (data not shown). We used this cell line as a normal standard in Northern blots when normal MNL RNA was in short supply.…”
Section: Methodsmentioning
confidence: 99%
“…The identified 743 highconfidence peaks represent putative genomic p53 binding sites in IMR90 fibroblasts 29 treated for 6 h with 5-fluorouracil (5-FU). After comparing these with binding sites previously reported in the cancer cell lines HCT116 23 and U2OS, 24,25 we found that the p53 sites in the normal fibroblasts reside in a distinct genomic landscape significantly different from that previously reported in the cancer cells, pointing at chromatin as a critical factor in the selection of the occupied sites.…”
Section: Distinct P53 Genomic Binding Patterns In Normal and Cancer-dmentioning
confidence: 99%